Heterogeneity of alleles encoding high- and low-prevalence red blood cell antigens across Africa: useful data to facilitate transfusion in African patients. - (:unkn) unknown (My University, 2013)
: Ethnic variations in red blood cell (RBC) antigens can be a source of alloimmunization, especially in migrant populations. To improve transfusion safety in continental Africa and countries with African migrants, we performed RBC genotyping to determine allele frequencies coding for high- and low-prevalence antigens. A total of 481 blood samples were collected in ethnic groups from West, Central and East Africa. Molecular typing was performed using a polymerase chain reaction - reverse sequence specific oligonucleotide method. Results demonstrated no DI*1, DI*3, YT*2, SC*2, LW*7, KN*2 alleles in any sample and the CO*2 allele was rare. The frequency of LU*1 was comparable to that of European-Caucasians (2%) except in Biaka pygmies (8%). The frequency of CROM*-1 was high in Mbuti pygmies (13%). High frequency of KN*7 and KN*6 may reflect selection pressure in the countries investigated. Analysis of Dombrock allele patterns confirmed uneven distribution of the DO*1 and DO*2 alleles with high frequencies of DO*-4 and DO*-5 in all groups. Altogether, findings demonstrated extensive allele-frequency heterogeneity across Africa and suggested that knowledge of patient ethnicity gives information about the high-prevalence antigens that may be lacking. These data are medically useful to support transfusion care of African migrants living in countries where the majority of the population is from a different ethnical background.
Keywords: African Research